Facile synthesis of large-area and highly crystalline WS2 film on dielectric surfaces for SERS - Li, Zhen; Jiang, Shouzhen; Xu, Shicai; Zhang, Chao; Qiu, Hengwei; Chen, Peixi; Gao, Saisai; Man, Baoyuan; Yang, Cheng; Liu, Mei (Journal of alloys and compounds, 2016)
A facile fabrication of high-quality and large-area tungsten disulfide (WS2) layers is demonstrated using a thermal decomposition of tetrathiotungstates ((NH4)2WS4) with two annealing process. During synthesis, the first annealing step is utilized to achieve lateral epitaxial growth of the WS2 and create seamless and large-area WS2 film. The second annealing step can offer an S-rich and high temperature condition, which is beneficial for the high quality of the WS2 film. Scanning electron microscopy, Raman spectroscopy and atomic force microscopy confirm the presence of large-area and high-quality WS2 film. The crucial role of the S, H2 and the effect of the temperature during the experiment are also investigated. Furthermore, the potential application of the prepared WS2 as a substrate for Raman enhancement is first discussed using R6G molecules as probe molecule. •A method to synthesize large-area and high-quality WS2 thin film is offered.•The crucial role of the sulphur and H2 during the experiments is investigated.•Obvious SERS and fluorescence quenching effect of the WS2 film is exhibit.